2015
DOI: 10.1121/1.4906262
|View full text |Cite
|
Sign up to set email alerts
|

Loudness of low-frequency pure tones lateralized by interaural time differences

Abstract: Directional loudness is that phenomenon by which the loudness of a sound may vary according to the localization of its source. This phenomenon has been mainly observed for high-frequency sounds, for sources located in the horizontal plane. Because of the acoustic shadow of the head, the left and right ear pressures are modified depending on the source azimuth and the global loudness resulting from a summation process may vary accordingly. Directional loudness has also been reported to occur at 400 Hz, where sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 17 publications
2
16
2
Order By: Relevance
“…This eect is very similar to the one already observed [6]. As the PSE is signicantly lower when ITD = ±772 µs than when ITD = 0 µs, it can be inferred that, at the same level, the dichotic signals are louder than the diotic signal.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…This eect is very similar to the one already observed [6]. As the PSE is signicantly lower when ITD = ±772 µs than when ITD = 0 µs, it can be inferred that, at the same level, the dichotic signals are louder than the diotic signal.…”
Section: Resultssupporting
confidence: 72%
“…In a previous study, an eect of interaural time dierence (ITD) on loudness has been shown for low-frequency pure tones at 200 and 400 Hz [6]. A small but signicant increase of loudness with increasing ITD could be observed at a low loudness level (40 phon) but not a moderate one (70 phon).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations